Analysis of bacteria clostridium perfringens on Tembakul (periopthalmodon schlosseri) in the coastal Waters of the district of west dumai - Indra Bayu Pratama; Dessy Yoswaty; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The experiment was conducted in November 2013 in the coastal waters ofthe Western District of Dumai. The method used in this study is a survey method,with the observation, measurement and sampling in the field. This study aims toanalyze the distribution of C. perfringens bacteria on tembakul in coastal watersof the District of West Dumai. Tembakul obtained around the mangrove forest inthe Purnama Village, which is divided into 3 stations namely Masjid estuary,mangrove forest on the Dermaga Street and Surrounding Fish Auction (TPI).Observations quality of coastal waters such as temperature, acidity (pH), andsalinity were measured directly at each sampling location. The results of thecalculation of C. perfringens bacteria analysis on tembakul (Periopthalmodonschlosseri) at three stations in the coastal waters of the District of West Dumairanged from 4.0 x 104 to 2.0 x 106 cfu / ml. Coastal waters of the District of WestDumai is still below the bacteriological contamination threshold, where theaverage total C. perfringens bacteria on fish that pass tembakul no threshold106 cfu/ml, which can lead to illness or poisoning the marine fishery products inDumai.Keywords : Dumai,Clostridium perfringens,Periopthalmodon schlosseri,Analysis